Hilaiditi Syndrome: Rare and Demonstrative (Based on own clinical observations) - V. M. Rudichenko; A. S. Lyubchenko; D. V. Reizin; N. V. Snigir (Medicine of Ukraine, 2026)
Chilaiditi syndrome is a rare condition characterized by the interposition of the intestine between the liver and the right hemidiaphragm. The article discusses its clinical manifestations, risk factors, diagnostic methods, and treatment approaches. A clinical case is presented in which Chilaiditi syndrome was detected during radiographic examination. The importance of timely recognition of this condition for differential diagnosis and prevention of unnecessary surgical interventions is emphasized.